Factors Influencing Community Segmentation and Participation in Ecotourism of Bali Barat National Park. - I. Wayan Koko Suryawan; Sapta Suhardono; Vania Dian Gunawan; Chun-Hung Lee; Van Viet Nguyen; Ari Rahman (Pertanika Journal of Social Sciences & Humanities, 2025)
This study provides an in-depth analysis of the factors influencing local community segmentation and participation in ecotourism initiatives within Bali Barat National Park, a protected area. Using logistic regression, the analysis explores how stakeholder engagement, operational performance, strategic importance, economic incentives, community tenure, and tourism occupancy predict active involvement. The results indicate that stakeholder engagement is the most significant positive predictor, suggesting that fostering community involvement is key to enhancing participation. Operational performance, particularly in asset management and organizational flexibility, also has a notable impact, though its influence is slightly weaker. In contrast, the strategic importance assigned to ecotourism activities has no significant impact on participation decisions. Economic incentives, such as earning above the minimum wage, play a critical role, with a high odds ratio indicating a strong likelihood of individuals. Community tenure, or the length of residency, shows a positive correlation with participation, highlighting the importance of long-term relationships in fostering engagement in ecotourism. The most notable finding is the significant effect of tourist-related occupancy on participation, with the odds ratio suggesting that visible benefits from ecotourism act as a powerful incentive for community involvement. The model's predictive accuracy (70.88%) and the Nagelkerke R Square value (0.603) indicate a strong fit and reliability. These findings provide valuable insights for developing targeted ecotourism policies that align with community characteristics, aiming to maximize engagement and promote sustainable practices within protected areas.